Penegakan Hukum Tindak Pidana Terhadap Cyber Bullying Dalam Perspektif Hukum Pidana - Intan Kumala Dewi; Sandra Dewi; Oksep Adhayanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The background to this problem is how the Criminal Law provisions regulate cyberbullying, what are the perpetrators' approaches to carrying out cyberbullying actions, and what factors influence perpetrators to carry out cyberbullying. The aim of this research is to analyze the applicable criminal law provisions related to cyber bullying, evaluate law enforcement against perpetrators of cyber bullying in Indonesia, and identify factors in cyber bullying. The method in this research is normative legal research. This approach is carried out by considering the contents of the ITE law, the analysis of which is carried out in more depth in relation to the problem of studying legal provisions. The result: Even though in the Criminal Code this matter has been formulated into different articles, the offense of insulting in the Criminal Code can be linked to Article 27 paragraph (3) concerning criminal acts of insulting via cyberspace. The approach taken by cyberbullying perpetrators is as follows: Instincts of cyberbullying perpetrators, First informant, one of the cyberbullying perpetrators, Cyberbullying perpetrators' actions through drive theory. Cyberbullying behavior is influenced by external and internal factors, including parental involvement, the school environment, as well as provocation and support. However, the main problem underlying cyberbullying is the perpetrator's sense of arrogance and superiority. Many cases of cyberbullying occur because the perpetrator feels more powerful and above other people. This can happen because social media is used unwisely, so they feel they can carry out inappropriate actions anonymously. Cyberbullying has a very bad impact on the mental and emotional health of victims. Therefore, there needs to be better awareness and education regarding the wise and responsible use of social media. Apart from that, there is also a need for strict supervision and action against perpetrators of cyberbullying. In this way, it is hoped that cases of cyberbullying can be reduced and society can use technology positively and have a good impact on life and social interactions.